Elaboración de un manual de funciones y un reglamento de admisión y empleo para el talento humano de la cooperativa de ahorro y crédito “Crediamigo” de la ciudad de Loja - Rojas González, Rita Paulina (2016)
Cooperativa de ahorro y Crédito "Crediamigo" of Loja's city, aims to social - lending, is at the service of men and women in general, support with credit, training, assistance and promote comprehensive development. Similarly, personnel administration is a code on ways to organize and trying individuals at work, so that each of them can reach greater realization of intrinsic abilities, achieving maximum efficiency, providing optimal results to the company. The business problems of this institution, lies mainly in the area of human talent, since it lacks a manual functions and rules for admission and employment, resulting in disruption of functions and admission of employment, causing disorder in the administrative activities; In addition, there is no formal documents indicating the steps to be followed in each of the processes, generating disruption in compliance, I waste lot of time and effort in administrative work. This research work was developed in the city of Loja, whose general objective was to perform a Manual of classification of posts and regulation of admission and employment of human talent for the workforce of the cooperative savings and credit "Crediamigo" from the city of Loja" Was one interview with the Manager of the cooperative with what was achieved to collect information about General and historical data of the cooperative by identifying the beginning of the operation in the city of Loja and establishing the number of employees, administrative levels and operating, allowing you to perform the internal administrative-level analysis, identifying the reality in which human talent management is demonstrating that it does not have an organizational structure defined and established. In the internal analysis, a survey was applied to 10 employees of the cooperative, identifying the problems and benefits provided by the cooperative. On the basis of this analysis was to review the most relevant conditions of administrative and operational staff and is presented the proposal for the elaboration of a Manual of classification of position and regulation of admission of employment, which determines the functions to management and operational level, defining the name of the position, relationships, roles and responsibilities. The proposal for a regulation for admission and employment, identifies four stages that must be followed for the hiring of staff, either by external and internal level of the cooperative, taking as an example the scheme established by the Ministry of labour, since as a strategy, the company must publish their administrative processes